1978
DOI: 10.1084/jem.148.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Site of action of serum factors that block delayed-type hypersensitivity in mice.

Abstract: Delayed-type hypersensitivity (DTH) 1 develops without adjuvant if the dose of SRBC given is appropriate to the route of inoculation (1). Increasing the amount of antigen reduces and eventually abolishes all evidence of DTH. Animals blocked by an excessive dose of SRBC cannot be subsequently sensitized, even when an optimal dose of antigen is given subcutaneously, the most reliable route for inducing DTH in the mouse. DTH does develop, however, when a massive intravenous dose of antigen is given to splenectomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…TSUNEKAWA et al [7] reported that in PPD-negative MP patients the number of peripheral blood T-lymphocytes was not significantly lower, but blastogenic lymphocyte response to PPD and PPDinduced IFN-γ production were significantly reduced compared with PPD-positive patients. LAGRANGE et al [19] suggested that cutaneous tuberculin anergy could result if the number or activity of circulating committed T-cells was depressed, and cutaneous anergy has been demonstrated to result from circulating suppressor cell. Previous data support the role of the suppressor cells, monocytes or macrophages in impairing CMI reactivity and delayed hypersensitivity to PPD at sites distant from the active focus, without inhibiting the appropriate response in the area of inflammation [15,20].…”
Section: Discussionmentioning
confidence: 99%
“…TSUNEKAWA et al [7] reported that in PPD-negative MP patients the number of peripheral blood T-lymphocytes was not significantly lower, but blastogenic lymphocyte response to PPD and PPDinduced IFN-γ production were significantly reduced compared with PPD-positive patients. LAGRANGE et al [19] suggested that cutaneous tuberculin anergy could result if the number or activity of circulating committed T-cells was depressed, and cutaneous anergy has been demonstrated to result from circulating suppressor cell. Previous data support the role of the suppressor cells, monocytes or macrophages in impairing CMI reactivity and delayed hypersensitivity to PPD at sites distant from the active focus, without inhibiting the appropriate response in the area of inflammation [15,20].…”
Section: Discussionmentioning
confidence: 99%
“…In that type of anergy, as in sarcoidosis, reactivity can be restored by concurrent administration of hydrocortisone (179). Antigen-specific depression of reactivity to tuberculin can be induced in mice by administration of high doses of mycobacterial antigens (217). In another study, however, injection of mice with BCG caused depression of unrelated DTH reactivity in mice (218).…”
Section: Immunological Correlates Of Cutaneous Anergymentioning
confidence: 91%
“…The technical factors that cause erroneous interpretations of tuberculin tests may have a role in falsely negative tuberculin tests in clinical settings (124,254,255). Mackaness suggested that cutaneous anergy could result if the number or activity of circulating committed T-cells was depressed (217,231). If this happens, the response to antigen at clinically irrelevant sites could be impaired, whereas that at the site of inflammation may be normal.…”
Section: Causes Of Nonreactive Tuberculin Tests In Patients With Tubementioning
confidence: 99%
See 2 more Smart Citations